PROGRAM SKRINING DETEKSI AWAL GANGGUAN TIDUR DI KOMUNITAS YOGA DHSP BALI, BANJAR SINGIN, SELEMADEG, KABUPATEN TABANAN - Anak Agung Dwi Ratih Arningsih; Putu Setiani; Agung Setiabudi; I Gede Eka Agung Agastya Punia; Komang Jaya Andika (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Sleep disorders are a health problem that is increasing in society and has a significant impact on the quality of life, productivity, and mental and physical health of individuals. Early detection of sleep disorders at the community level is a strategic step to prevent long-term complications. The program aims to identify individuals at risk of sleep disorders through screening using valid instruments such as the Insomnia Severity Index (ISI). The activity was carried out with an educational and participatory approach, involving sleep health counselling and filling out screening questionnaires independently by participants. The results of the program showed that some community members experienced early symptoms of sleep disorders that could be followed up with referral or promotive and preventive interventions. This program proves the importance of sleep health education and the effectiveness of early screening in identifying at-risk populations and strengthening public awareness of the importance of healthy sleep patterns.